2001
DOI: 10.1038/ncb1001-939
|View full text |Cite
|
Sign up to set email alerts
|

Proteins containing the UBA domain are able to bind to multi-ubiquitin chains

Abstract: The UBA domain is a motif found in a variety of proteins, some of which are associated with the ubiquitin-proteasome system. We describe the isolation of a fission-yeast gene, mud1+, which encodes a UBA domain containing protein that is able to bind multi-ubiquitin chains. We show that the UBA domain is responsible for this activity. Two other proteins containing this motif, the fission-yeast homologues of Rad23 and Dsk2, are also shown to bind multi-ubiquitin chains via their UBA domains. These two proteins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
356
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(379 citation statements)
references
References 19 publications
22
356
0
1
Order By: Relevance
“…Several lines of evidence support this receptor hypothesis. In rad23 and dsk2 mutant cells, substrates are ubiquitinated but not degraded, consistent with a role in substrate delivery (Lambertson et al, 1999;Wilkinson et al, 2001;Chen and Madura, 2002;Funakoshi et al, 2002;Rao and Sastry, 2002;Saeki et al, 2002a). Moreover, both the UbL and UBA domains of Rad23 are essential for its role in promoting proteolysis (Bertolaet et al, 2001b;Lambertson et al, 2003;Rao and Sastry, 2002).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Several lines of evidence support this receptor hypothesis. In rad23 and dsk2 mutant cells, substrates are ubiquitinated but not degraded, consistent with a role in substrate delivery (Lambertson et al, 1999;Wilkinson et al, 2001;Chen and Madura, 2002;Funakoshi et al, 2002;Rao and Sastry, 2002;Saeki et al, 2002a). Moreover, both the UbL and UBA domains of Rad23 are essential for its role in promoting proteolysis (Bertolaet et al, 2001b;Lambertson et al, 2003;Rao and Sastry, 2002).…”
Section: Introductionmentioning
confidence: 90%
“…On the contrary, recent work has shown that a diverse set of ubiquitin-binding receptors regulate the targeting of ubiquitinated proteins to the proteasome in a substratespecific manner (Wilkinson et al, 2001;Chen and Madura, 2002;Elsasser et al, 2004;Verma et al, 2004; for review, see Elsasser and Finley, 2005;Hicke et al, 2005). The first polyubiquitin-binding receptor identified was Rpn10, a subunit of the 19S regulatory complex that contains a ubiquitin-interacting motif (Deveraux et al, 1994 tional ubiquitin chain recognition mechanisms must exist (van Nocker et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…or linear [104][105][106][107][108]. A large study by Raasi and coworkers pinpointed the specificity of 30 of these domains [109].…”
Section: Tandem Ubiquitin Binding Entity (Tube) Based Enrichmentmentioning
confidence: 99%
“…Budding yeast Dsk2 is a UBL-UBA protein that helps deliver polyubiquitinated proteins to the proteasome [17][18][19]. To better understand the molecular mechanisms of UBL-UBA proteins in the ubiquitin-proteasome pathway, we investigated the role of Dsk2 ubiquitination using lysine mutants of the Dsk2 UBL domain.…”
mentioning
confidence: 99%